Research progress on riveting processes of low-ductility light alloys for carrier tools: a comprehensive review - Du, Zhanpeng; Rui, Shili; Ma, Baolin; Meng, Xiangxin; Ren, Lifang; Xu, Liguo; Yao, Feng; Yu, Dongzheng; Cao, Can (Frontiers in Materials, 2025)
Energy shortage is a significant challenge faced by humanity, and energy conservation and carbon reduction are a common choice for global sustainable development. Among them, improving the lightweight level of carrier tools is a key way to promote global energy conservation and carbon reduction. Low-ductility light alloys have been gradually applied in the lightweight design of carrier tools due to their characteristics of high strength and low density. However, due to the large differences in physical properties such as melting points between low-ductility light alloys and high-strength steels, it is difficult to achieve effective connection of multi-material vehicle bodies, which limits the further promotion and application of low-ductility light alloy materials. As a cold joining technology, the riveting process has become an important means to support the mass application of low-ductility light alloy materials. In traditional riveting processes, solid rivets improve the uniformity of deformation by optimizing geometric and process parameters; blind rivets enhance the practicality of single-sided operation by regulating mandrel tension and deformation rate to suppress brittle fracture. New processes are constantly innovated: for example, self-piercing riveting without pre-opening reduces damage to the base material; pre-holed self-piercing riveting improves the bearing capacity of multi-layer dissimilar materials; adhesive-riveted hybrid joining has the advantages of strong bearing capacity and reliable connection; friction self-piercing riveting realizes the dual strengthening of “mechanical interlocking - solid-state joining” by softening materials through frictional heat; electromagnetic riveting improves the uniform deformation of materials through high strain rate dynamic loading. However, due to the low elongation and high sensitivity of low-ductility light alloy materials, the joints are prone to process-induced damage such as macroscopic cracks, which affect the forming quality and mechanical properties of the joints. Thus, it is necessary to deepen mechanism research, promote process optimization, expand the path of performance improvement in various environments, and promote the high-quality development of lightweight carrier tools.